CIVILIZATIONAL AND EPISTEMOLOGICAL INCLUSIVISM AS THE BASIS OF COSMOPOLITAN ISLAMIC EDUCATION A PROGRESSIVE MUSLIM PERSPECTIVE - Abdi, Supriyanto (Khazanah: Jurnal Studi Islam dan Humaniora, 2025)
The relationship between Islamic and Western civilization has been subjected to ongoing heated debate among Muslim and non-Muslim scholars alike. This paper aims to examine the views of progressive Muslim thinkers in debunking the binary construction of Islamic and Western civilizations, as well as their underlying epistemologies, that often underpin the contemporary debate on this issue. Combining theoretical investigation and thematic content analysis of the works of leading progressive Muslim thinkers, it seeks to examine how the idea of civilizational and epistemological inclusivism provides a stronger foundation for revitalizing the cosmopolitan spirit within Islamic thought and education today. The paper argues that in the increasingly interconnected and globalized world today, civilizational and epistemological inclusivism as advocated by progressive Muslim thinkers is critical in enhancing the participation and contribution of Muslims in reshaping the world order that is more just, dialogical, and capable of effectively tackling global humanitarian and ecological challenges.